The Effects of Thyroid Hormone Levels on Patent Ductus Arteriosus Closure in Newborns - Basak KAYA; Hasan AKDUMAN; Dilek DILLI; Semra CETINKAYA; Ahmet OKTEM; Utku Arman ORUN; Mehmet TASAR; Aysegul ZENCIROGLU (Medeniyet Medical Journal)
Objective: Although the role of thyroid hormones in functional and anatomical closure of patent ductus arteriosus (PDA) is well known, their effects on the medical or surgical closure of PDA in newborns remain unclear. This study aimed to assess the correlation between thyroid function tests and PDA closure through medical or surgical interventions in newborns. Methods: This retrospective study was conducted on 65 newborns diagnosed with hemodynamically significant PDA (hs-PDA), with a premature rate of 81.5% (n=53). The subjects were divided into two groups according to the nature of the ductal closure as medically responsive 'MR-PDA' or surgically treated 'ST-PDA'. The groups were compared in terms of thyroid hormone levels and other clinical parameters. Results: Thirty-three (51%) of all 65 patients had PDA and responded to medical treatment. Gestational week, birth weight, and mode of delivery were similar between the medical and surgical treatment groups (p>0.05). Free thyroxine levels were significantly lower in the MR-PDA group than in the ST-PDA group (p=0.01). Conclusions: Because hs-PDA is associated with increased morbidity and mortality in the neonatal period, especially in premature infants, we hypothesize that thyroid hormone levels may play a role in the closure of hs-PDA.